THE COMPREHENSION STUDY OF AFRICAN AMERICAN VERNACULAR ENGLISH AND WHITE AMERICAN VERNACULAR ENGLISH IN THE INDONESIAN SUBTITLES OF THE FILM 8 MILE - Eriana Crista br Tambunan; Febrina S.L Lumbantobing; Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the translation of vernacular language in the Indonesian subtitles of 8 Mile, focusing on linguistic features, subtitling strategies, and identity representation shifts. The research aims to identify the types of vernacular varieties used in the film, analyze the subtitling strategies applied in translating those varieties, and investigate how such strategies affect the representation of social identity in the target language. This study employs a qualitative descriptive method with a sociolinguistic and audiovisual translation approach. The data consist of 60 selected utterances containing vernacular features, particularly African American Vernacular English (AAVE) and White American Vernacular English (WAVE). The data were collected through observation and documentation techniques and analyzed using linguistic classification and subtitling strategy frameworks. The findings reveal that AAVE features dominate the dataset, including double negation, non-standard subject verb agreement, and the use of “ain’t.” WAVE features are primarily phonological reductions and informal lexical expressions. In translating these vernacular forms into Indonesian, the dominant subtitling strategies identified are leveling, neutralization, softening, omission. Among these, structural normalization through leveling and neutralization appears most frequently.   Furthermore, the analysis of identity representation shift indicates that leveling is the most dominant outcome, followed by loss, while preservation occurs in limited cases. Although the subtitles generally maintain semantic meaning and narrative coherence, they significantly reduce sociolinguistic markedness. As a result, the linguistic features that function as markers of racialized and subcultural identity in the source language become less explicitly represented in the target language. This study concludes that the translation of vernacular language in audiovisual media is not merely a linguistic transfer process but a mediated reconstruction shaped by structural, technical, and ideological constraints. While narrative meaning is preserved, sociolinguistic distinctiveness is partially reduced in the Indonesian subtitles.